A new class of biological ion-driven rotary molecular motors with 5:2 symmetry - Rieu, Martin; Krutyholowa, Roscislaw; Taylor, Nicholas M. I.; Berry, Richard M. (Frontiers in Microbiology, 2022)
Several new structures of three types of protein complexes, obtained by cryo-electron microscopy and published between 2019 and 2021, identify a new family of natural molecular wheels, the “5:2 rotary motors.” These span the cytoplasmic membranes of bacteria, and their rotation is driven by ion flow into the cell. They consist of a pentameric wheel encircling a dimeric axle within the cytoplasmic membrane of both gram-positive and gram-negative bacteria. The axles extend into the periplasm, and the wheels extend into the cytoplasm. Rotation of these wheels has never been observed directly; it is inferred from the symmetry of the complexes and from the roles they play within the larger systems that they are known to power. In particular, the new structure of the stator complex of the Bacterial Flagellar Motor, MotA5B2, is consistent with a “wheels within wheels” model of the motor. Other 5:2 rotary motors are believed to share the core rotary function and mechanism, driven by ion-motive force at the cytoplasmic membrane. Their structures diverge in their periplasmic and cytoplasmic parts, reflecting the variety of roles that they perform. This review focuses on the structures of 5:2 rotary motors and their proposed mechanisms and functions. We also discuss molecular rotation in general and its relation to the rotational symmetry of molecular complexes.